Femmes, genre, migration et mobilités - Catarino, Christine; Morokvasic, Mirjana (Revue européenne des migrations internationales, 2005)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; antiracisme; approches et analyses; cours; discipline; europe; france; féminisme décolonial; inégalités; migration; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques

Les avancées de la conférence de Beijing profitent-elles réellement aux femmes? - Duplan, Daphnée (Université du Québec à Montréal, 2005)
Keywords: 1900-1999; 1990-1999; IREF; ONU; approches et analyses; discipline; droits des femmes*; inégalités; mémoires/thèses; périodes historiques; science politique; science politique et droit; systèmes d'oppressions; thématiques

La réflexion queer : apports et limites - Lamoureux, Diane (Dialogues sur la troisième vague féministe, 2005)
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; fem1000; histoire et politique; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Pour en finir avec l'homophobie - Picquart, Julien; Fassin, Eric (L. Scheer, 2005)
Dénonce les différentes formes prises par l'homophobie au quotidien et met en lumière l'impact de cette forme de violence sociale. Etudie les enjeux de la pénalisation et de la prévention de l'homophobie et de la garantie des mêmes droits pour les hétérosexuels et les homosexuels.
Section: 187 pages ; 21 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; homophobie; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Aimez-vous le queer? - Schehr, Lawrence R. (Rodopi, 2005)
Lawrence Schehr's introduction to this collection of essays covers key landmarks in twentieth-century representations of homosexuality in French literature and culture. Beginning with Gide's and Proust's classical and aristocratic representations of homosexuality, subdued within discourses of power and language consonant with the turn of the century, Schehr proceeds to identify the literary and cinematic innovations of Cocteau and Genet as united in their respective revolt against the totalizing structures and discourses of their illustrious predecessors. After discussing the Second World War, the consumerism of the 1960s, and the emerging ‘culture gay’, Schehr fast-forwards to the advent of the paradox of queer theory in the 1990s, highlighting its theoretical (mis)appropriations, from the positive critique of heteronormativity to its insignificance ‘pour le séropositif mourant dans un lit d'hôpital’ (p. 10), acknowledging along the way that queer theory is both ‘made in the USA’ (p. 11) and subject to that continent's imperializing tendencies and ancillary oversights. The editor promises queer readings of French literature and film, but then proffers post-queer readings. Many of the contributions are stimulating and rich in insights. Owen Heathcote's study of the military uniform as both mask and precursor of the collapse of masculinity in novels by Balzac and the cinema of Claire Denis earmarks the uniform as the queerizing stuff of maleness. James Williams's exploration of Jean Cocteau's influence on the cinema of Jean-Luc Godard also unearths a queerization at the heart of Godard's aesthetic creation. In a fascinating contribution, Elizabeth Stephens deconstructs the ‘wall’ of repression and solitude (and its associations with closeted representations of homosexuality) in order to expose the ‘fissures dans les murs genetiens’ (p. 133), demonstrating how Genet subverts categories of heteronormative language in the pursuit of repressed homoerotic desire. Drew Jones conducts a thoroughly lucid exegesis of the distinction between sexual desire (act) and homosexual ‘identity’ in Genet's Querelle de Brest. Countering the Sartrean notion that Genet's treatment of homosexuality (as value in crime and disgust against authority) is not existential (‘homosexuel en soi’ but not ‘pour soi’), Jones argues that Querelle breaks free of essentialist homosexuality by resisting the naming and categorizing hegemony of an Identity as ‘pederast’ that society has conferred on him. It would have been a treat to see how this collection would have evolved had the ‘projet scientifique’ first envisaged been followed through; this ‘projet’ clearly reflected the earlier symmetry of Schehr's tripartite schematization of homosexual cultural production from Proust to queer, but I suspect would have given the collection a different direction. The articles are the collection's real focus, and their value for students and academics with interests in gay and lesbian cultural production in France is unquestionable.
Section: 158 pages ; 24 x 17 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques